PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENERAPKAN PENDIDIKAN MULTIKULTURAL DI SEKOLAH MENENGAH ATAS NEGERI (SMAN) PERKOTAAN JOMBANG JAWA TIMUR - Waslah Waslah; Elik Khoirun Nisa (AT-TURATS, 2018)
Abstract This study examines the diversity that exists in schools, the concept of multicultural Islamic education, as well as the role of Islamic Education Teachers in applying multicultural education in senior high school (SMAN) Perkoataan Jombang East Java Indonesia. This is because of the author's interest in this theme. Multicultural education is still limited to the concept and theory alone, the author tries to be drawn in life and practice. This research uses qualitative approach with field study design (Field Research), which takes the object of SMA Negeri 1 Jombang East Java. In this study, researchers used the method of observation, interview and documentation to collect the required data. Data analysis is done by giving meaning to the data collected and from that meaning will be taken conclusion. The conclusions that can be drawn from this research are 1). The existing condition in urban high school in Jombang is very diverse. Such diversity includes the ethnic diversity, religion, social status and mindset. Schools give each individual the freedom to actualize according to what they want. 2) Multicultural religious education is an educational model that emphasizes moral values, such as compassion, one's love, help, tolerance, appreciate the diversity and nature of mutual respect for humanity. 3) The role of PAI teachers in applying the existing multicultural education has been in accordance with what is the purpose of multicultural education. It is based on teaching and learning activities that take place in the school. Keywords: PAI Teachers in Urban High School